2007
DOI: 10.1677/jme-06-0054
|View full text |Cite
|
Sign up to set email alerts
|

A combined approach identifies a limited number of new thyroid hormone target genes in post-natal mouse cerebellum

Abstract: Thyroid hormones act directly on gene transcription in the post-natal developing cerebellum, controlling neuronal, and glial cell differentiation. We have combined three experimental approaches to identify the target genes that are underlying this phenomenon: 1) a microarray analysis of gene expression to identify hormone responsive genes in the cerebellum of Pax8 K/K mice, a transgenic mouse model of congenital hypothyroidism; 2) a similar microarray analysis on primary culture of cerebellum neurons; and 3) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 65 publications
(43 reference statements)
1
25
0
Order By: Relevance
“…A global analysis of TH target genes has not been performed in the adult mammalian retina. However, in the adult rodent brain, relatively few TH-dependent genes have been identified, with no apparent involvement of components of the chromatin modification pathway (Quignodon et al, 2007). This opens the possibility that transactivators of S-and M-opsin with regulatory function during early development also play a role for the maintenance of opsin identity in mature cones.…”
Section: Discussionmentioning
confidence: 99%
“…A global analysis of TH target genes has not been performed in the adult mammalian retina. However, in the adult rodent brain, relatively few TH-dependent genes have been identified, with no apparent involvement of components of the chromatin modification pathway (Quignodon et al, 2007). This opens the possibility that transactivators of S-and M-opsin with regulatory function during early development also play a role for the maintenance of opsin identity in mature cones.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts to identify target genes that are directly regulated by thyroid hormone during brain development have been made with limited success (Dong et al, 2005;Quignodon et al, 2007a;Diez et al, 2008;Royland et al, 2008). As one obstacle, the (G/A)GGT(C/G)A consensus sequence of the TRE that usually contains this motif as two half sites arrayed as either direct repeats spaced by four nucleotides, inverted repeats spaced by six nucleotides or as palindromes (reviewed in Yen, 2001) is quite frequent, and bioinformatic approaches usually will reveal a large number of them.…”
Section: Molecular Targets Of Thyroid Receptorsmentioning
confidence: 99%
“…Candidates for such a function are BTEB (Denver and Williamson, 2009), hairless (hr) (Potter et al, 2002), NeuroD (Chantoux and Francon, 2002), RORalpha (Koibuchi and Chin, 1998) and NGFI-A (Egr1) (Mellstrom et al, 1994). Moreover, recent approaches to identify further thyroid hormone regulated gene products in the brain using microarray analysis revealed additional T3 target genes (Poguet et al, 2003;Dong et al, 2005;Quignodon et al, 2007a;Diez et al, 2008). However, their exact function during neuronal differentiation still needs to be established.…”
Section: Molecular Targets Of Thyroid Receptorsmentioning
confidence: 99%
“…Finally, THs influence the expression of cytoskeletal components, important mediators of morphological differentiation, as well as axonal and dendritic outgrowth (Silva and Rudas, 1990;Aniello et al, 1991a;Aniello et al, 1991b;Lorenzo et al, 2002). Only in a few examples has it been possible to assign the control of gene expression to a specific receptor subtype (Calza et al, 2000;Abel et al, 2001;Quignodon et al, 2007;Diez et al, 2008). Finally, a recent study identified the TR 1 binding sites and target genes in the developing mouse cerebellum through the use of the ChIP-onChIP technology (Dong et al, 2009).…”
Section: Gene Regulationmentioning
confidence: 99%